An evaluation of a university-based intensive English program:|Insights of students and teachers - Cengiz, Yusuf. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study evaluates a preparatory program in a private university in Istanbul, Turkey. Program weaknesses, strengths and points for improvement were uncovered through student and teacher interviews and focus groups. The data was coded, and emergent themes were analyzed and interpreted. The study revealed that students and teachers hold different opinions about the implementation and pace of the program. As this issue affects the perspectives and the motivations of the program, an extensive outcome evaluation is needed to justify and validate the implementation of the program. The data revealed that the high teacher quality, foreign instructors, content classes and portfolio tasks are the strengths of the program, along with the program’s contribution to students’ general language skills. The data also showed that a mismatch between the curriculum and the proficiency exam create an important caveat for the program; this was identified as the most important weakness. Additional weaknesses included the textbooks, the program’s unresponsiveness to plagiarized assignments, teachers’ being non-proficient in content areas, and physical constraints that prevent the successful implementation of content classes. Finally, areas for improvement are suggested: introducing proficiency-related classes towards the end of the term, cooperating with academic departments to introduce students to the academic world and its language, and conducting a material evaluation to find the best textbooks for specific context.
Keywords: English language -- Study and teaching -- Turkish students.; English teachers -- Training of -- Turkey.